Investigation on Dynamic Characteristics of AlGaN/GaN Lateral Schottky Barrier Diode - Haitao Zhang; Xuanwu Kang; Yingkui Zheng; Hao Wu; Ke Wei; Xinyu Liu; Tianchun Ye; Zhi Jin (Micromachines, 2021)
This work investigates the transient characteristics of an AlGaN/GaN lateral Schottky barrier diode (SBD) and its recovery process with a dedicated dynamic measurement system. Both static and dynamic characteristics were measured, analyzed with the consideration of acceptor/donor traps in the C-doped buffer and GaN channel, and verified by Silvaco TCAD (technology computer aided design) simulations. The energy band, electric field, and electron concentration were monitored in the transient simulation to study the origin of the current collapse in the SBD. Using the verified model, the impact of carbon doping concentration in the buffer and the thickness of the unintentionally doped (UID) GaN channel in the transient behavior was estimated. Several observations were revealed. Firstly, the traps in the GaN channel and buffer layer have a significant impact on the current collapse of the device. A severe deterioration of current collapse can be observed in the SBDs with increasing density of acceptor-like traps. Secondly, the current collapse increases with the thinner UID GaN channel layer. This well-performed simulation model shows promise to be utilized for the dynamic performance optimization of GaN lateral devices.